Relevansi Filsafat Pendidikan Imam Al-Ghazali terhadap Pendidikan Islam Kontemporer - Fariha Romadloniyah; Ihda Ulvi Ulia Muhasonah; Nayla Hikmah Khairun Nisa; M. Yunus Abu Bakar (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2026)
This study explores the relevance of Imam Al-Ghazali’s educational philosophy to contemporary Islamic education in responding to current moral, social, and educational challenges. Using a library research method, the study systematically examines Al-Ghazali’s views on educational goals, curriculum orientation, the role of teachers, and instructional methods, and then contextualizes these perspectives within the dynamics of modern educational systems. The analysis highlights how Al-Ghazali’s educational thought addresses issues related to moral decline, character formation, and the imbalance between intellectual achievement and ethical development in present-day education. The findings show that Al-Ghazali’s emphasis on integrating knowledge and character, balancing cognitive, affective, and psychomotor aspects, and highlighting the teacher’s role as a moral exemplar remains highly applicable today. His educational framework which prioritizes spiritual development, moral formation, self-discipline, and closeness to God offers a strong, comprehensive, and relevant foundation for renewing Islamic education in the modern era and for fostering holistic learners with intellectual competence, ethical awareness, and spiritual integrity.